TRIACYLGLYCEROL ESTER HYDROLASE ACTIVITY DURING METAMORPHOSIS OF ARMYWORM, MYTHIMNA SEPARATA (WALKER) - POL, J.J.; SALUNKHE, P. S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2002)
The changes in triacylglycerol ester hydrolase activity during metamorphosis of Mythimna separata have been studies. The enzyme activity was maximum at pH 7.6. The triacylglycerol ester hydrolase mainly hydrolysed the triglycerides and released fatty acids. The gradual increase in the triacylglycerol ester hydrolase activity from 1 to 3-day male and female pupae, decline from 3 to 6-day male and 3 to 5-day female pupae and gradual decrease from 6 to 10-day male and 5 to 10-day female pupae was observed. The maximum enzyme activity was observed in 6-day male and 5-day female pupae and minimum in 10-day male and female pupae. The physiological role of triacylglycerol ester hydrolase during metamorphosis of M. separata is discussed.